WACANA PEMGEMBANGAN MODEL PEMBELAJARAN KOOPERATIF MATA KULIAH DASAR-DASAR AKUNTANSI PADA PERGURUAN TINGGI - Lilis Sulistyani (STIE AUB Surakarta, 2014)
This paper aims to provide discourse models of co-operative learning courses basics of accounting to improve the skills of faculty and students at the college. Learning management courses basics of accounting with co-operative models for faculty are expected to improve the skills of faculty in teaching courses and basic accounting skills for students diharapkan students in the field of accounting will increase. To achieve these objectives, the learning stage is done by the Research and Development (R & D) in three stages. The first stage identifies co-operative learning models appropriate for courses basics of accounting. The second stage test models of cooperative learning courses basics of accounting in college to determine the increase faculty skills in teaching and improving the skills of accounting students. The third stage construct prototype models of co-operative learning courses basics of accounting, carried dissemination and implementation of models of cooperative learning courses basics of accounting through workshops and action research (classroom action research) in college. Based on the above planning activities, targeted results in learning techniques include: (1) models of co-operative learning courses basics of accounting; (2) implementation guidebook models of co-operative learning courses basics of accounting; (3) guidelines for assessment of learning courses basics of accounting with co-operative learning models; (4) disseminated models of co-operative learning courses basics of accounting to faculty, education policy makers, and (5) the use of the book co-operative learning models to improve the skills of faculty in teaching courses on the basics of accounting college. Keywords: Model, Learning, Co-operative, Accounting Basics.